Extracellular vesicles from human semen induce unique tolerogenic phenotypes in vaginal dendritic cells and regulatory T lymphocytes - Paktinat, Shahrokh; Gravett, Michael G.; Tobey, Cara; Kirby, Anna; Horner, Whitney; Shaffer, Rebecca; Fialkow, Michael; Nguyen, Nam Phuong; Gornalusse, Germán G.; Kalatehjari, Maryam; Hughes, Sean M.; Hladik, Florian; et al. (Frontiers in Immunology, 2025)
IntroductionThe regulation of immune responses to promote tolerance to the fetus is critical for successful pregnancy. An understudied aspect of this process is the initiation of regulation pre-conception via exposure to semen. Our study aimed to understand how semen impacts recipient dendritic cells (DCs) and their subsequent role in shaping CD4 T cell differentiation.MethodsMonocyte-derived DCs (MoDCs) were exposed to semen extracellular vesicles (SEV) or vesicle-depleted semen plasma (VDSP). Phenotypic and functional markers were analyzed using flow cytometry. We also exposed epithelial sheets from vaginal tissue to SEV and VDSP, and measured the number and marker expression of emigrating cells. Finally, we tested how SEV- or VDSP-exposed DCs altered CD4 T cell differentiation by co-culturing exposed MoDCs or tissue emigrated cells with autologous naïve CD4 T cells.ResultsMoDCs exhibited a significant increase of CD141, CD1a, CD38, and ILT4 expression when exposed to SEV or VDSP. A unique feature of semen-treated MoDCs was expression of indoleamine 2,3-dioxygenase (IDO), a potent contributor to the induction of regulatory T cells (Tregs). SEV but not VDSP significantly increased the emigration of intraepithelial DCs. Additionally, SEV significantly enhanced the expression of multiple immunoregulatory markers in the emigrated DCs. After co-culture, we observed significantly more FOXP3+ Tregs expressing high levels of TIGIT in the groups that were initially exposed to SEV.DiscussionThese findings indicate that exposure to SEV induces a tolerogenic program in DCs that can direct differentiation of a unique memory Treg subset, primed for expansion and presumably destined to support a successful pregnancy.